2017
DOI: 10.4274/jpr.74436
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Maternal Comfort of Sequential versus Simultaneous Breast Expression by Mothers of Critically III Newborns

Abstract: ABS TRACT ÖzAim: Expressed breast milk is beneficial for infants in neonatal intensive care unit (NICU) when direct breastfeeding is not possible. Breast expression with manual or electric breast pumps is promoted for the initiation and maintenance of lactation in this critical period. In this study, we aimed to compare the efficacy and maternal comfort of sequential versus simultaneous breast expression in newly delivered mothers whose infants were admitted to NICU. Materials and Methods: Thirty five mothers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The low agreement on this indicator may have been influenced by difficulty in evaluating comfort through a video, or by the observer considering the studied NICU environment. A neonatal unit may not provide enough space, adequate seats, and armrests for the breastfeeding mother to feel safe and comfortable (Hammarlund, Björk, Thelin, & Peterson, ; Köroğlu et al., ), which was the setting for the observations in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The low agreement on this indicator may have been influenced by difficulty in evaluating comfort through a video, or by the observer considering the studied NICU environment. A neonatal unit may not provide enough space, adequate seats, and armrests for the breastfeeding mother to feel safe and comfortable (Hammarlund, Björk, Thelin, & Peterson, ; Köroğlu et al., ), which was the setting for the observations in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies examined the effect of sequentially expressing one breast at a time versus simultaneous expression of both breasts on milk production. 26,33 One small observational study 33 found no difference in milk volume between simultaneous and sequential expression during the first 10 days postpartum in 35 mothers of infants 25 to 38 weeks' GA. However, the duration of expression sessions was shorter for simultaneous expression (11.57-15.62 minutes) than for sequential expression (18.16-20 minutes).…”
Section: Simultaneous Versus Sequential Expressionmentioning
confidence: 99%